Poznanie dramatyczne - Anna Krajewska (Przestrzenie Teorii)
The author describes the problem of dramatic cognition against the background of the concept of the dramatic model of literary studies arising from this discipline's own uncertainty about its research procedures, changes occurring within the literary theory discourse and the mechanisms of the theory of cognition concerning the cognition of art and the world. The author discusses application of the category of drama in the modern theory of literature. She also emphasises the fact of unsovability and transgression connected with the theatrical executive instruction of the drama, making it possible to show the play between the reality and the fictionality of the world expressed in the toposes of "theatre-picture", "theatre-figure of the world" and the model of "theatre without the world". The author also adduces the epistemological metaphors of the lamp, the mirror, and the screen.